2008
DOI: 10.1007/s00125-008-1016-x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-binding protein-1 in the prediction and development of type 2 diabetes in middle-aged Swedish men

Abstract: Aims/hypothesis Insulin-like growth factor-binding protein-1 (IGFBP-1) production in the liver is inhibited by insulin, and low circulating levels are associated with the metabolic syndrome. The aim of this study was to evaluate the predictive role and change in IGFBP-1 concentrations during development of abnormal glucose regulation. Methods IGFBP-1 levels were determined at baseline and at 10 years in an incident case-control prospective study of Swedish white men aged 35-56 years. Individuals with normal gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 50 publications
7
91
2
Order By: Relevance
“…In line with our previous reports, high IGFBP-1 concentrations predicted a reduced risk of diabetes in both men and women [17,18], and these effects were evident regardless of 25(OH)D serum concentrations. Interestingly, in the presence of low serum IGFBP-1 concentrations, high 25(OH)D concentrations did not predict a reduced risk of progression to , separately and in combination, associated with prediabetes at baseline in women (grey lines) and men (black lines).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our previous reports, high IGFBP-1 concentrations predicted a reduced risk of diabetes in both men and women [17,18], and these effects were evident regardless of 25(OH)D serum concentrations. Interestingly, in the presence of low serum IGFBP-1 concentrations, high 25(OH)D concentrations did not predict a reduced risk of progression to , separately and in combination, associated with prediabetes at baseline in women (grey lines) and men (black lines).…”
Section: Discussionsupporting
confidence: 92%
“…An alternative link between vitamin D and glucose homeostasis might be the IGF system [9]. We have shown that low serum levels of IGF-binding protein-1(IGFBP-1) in men and women with normal glucose tolerance (NGT) strongly predict risk of type 2 diabetes and prediabetes (impaired fasting glucose [IFG], impaired glucose tolerance [IGT] or the two combined) at a follow-up 8-10 years later [17,18]. In addition, a combination of high concentrations of 25(OH)D and IGF-1 has been associated with a low risk of the metabolic syndrome [19].…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] Low IGFBP1 levels predict the development of abnormal glucose regulation and have been associated with an unfavorable cardiovascular risk profile. 45,46 Conversely, in patients with acute myocardial infarction and type 2 diabetes, high IGFBP1 levels have been associated with an increased risk of cardiovascular mortality and morbidity, which is probably the result of hepatic insulin resistance in these patients. 47 As circulating IGFBP1 is generally considered to be of hepatic origin, the effect observed in this study is possibly the result of a modified IGFBP1 expression mediated by IGF2 in the liver.…”
mentioning
confidence: 99%
“…IGFBP1 is a marker of insulin sensitivity (20). In clinical and population studies, low circulating IGFBP1 concentration has been associated with insulin resistance (11,21) and an increased risk for incident gestational diabetes, glucose intolerance and type 2 diabetes (4, 10, 11, 22).…”
Section: Igfbp1 System In Health and Diseasementioning
confidence: 99%
“…IGF binding protein 1 (IGFBP1) is an acute modulator of IGF1 and IGF2 bioavailability, and altered IGFBP1 levels have also been linked to diabetes rates (10,11,12). IGFBP3 is the principal carrier protein of IGF1 and IGF2.…”
Section: Introductionmentioning
confidence: 99%